СHOICE OF ORTHOPAEDIC TREATMENT PATHOLOGICAL ABRASION OF HARD DENTAL TISSUES DEPENDING ON THE MORPHOLOGICAL STATE OF AREA IMPRESSION - Balya, G.N. (World of Medicine and Biology, 2013)
The proposed advanced technology of coating the prosthesis with additional fixing elements as vnutrishnodentalnyh locking fasteners.
Keywords: overdenture; fixation elements; pathological abrasion of hard dental tissues; dental defects